MANGROVE COMMUNITY STRUCTURE IN TELUK BELUKAR VILLAGE, NORTH GUNUNGSITOLI DISTRICT, GUNUNGSITOLI CITY NORTH SUMATRA - Januari Dawolo; Eliyunus Waruwu; Ridho Victory Nazara; Betzy Victor Telaumbanua; Putra Hidayat Telaumbanua; Destriman Laoli (RADJA PUBLIKA, 2024)
Mangrove forests are ecosystems that have ecological and economic functions. The ecological functions of mangrove forests include protecting coastlines, preventing sea water intrusion, habitat, feeding ground, nursery ground, spawning ground for aquatic biota and as a climate regulator. micro. This research aims to determine the structure of the mangrove community and mangrove density. This research was conducted in Teluk Belukar Village, North Gunungsitoli District, North Gunungsitoli City, North Sumatra in August 2023. Research activities were carried out by creating a plot measuring 10x10 m2. Each plot contains the size categories of tree (10x10 m2), sapling (5x5 m2) and seedling (1x1 m2). There are 24 types of mangroves found at the research location. The highest value of mangrove species density (Di) obtained at the research location was at the seedling level of 160,000 ind/ha.